2014
DOI: 10.1155/2014/963264
|View full text |Cite
|
Sign up to set email alerts
|

Filters in 2D and 3D Cardiac SPECT Image Processing

Abstract: Nuclear cardiac imaging is a noninvasive, sensitive method providing information on cardiac structure and physiology. Single photon emission tomography (SPECT) evaluates myocardial perfusion, viability, and function and is widely used in clinical routine. The quality of the tomographic image is a key for accurate diagnosis. Image filtering, a mathematical processing, compensates for loss of detail in an image while reducing image noise, and it can improve the image resolution and limit the degradation of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…However, with higher cutoff frequency, the image revealed two more pairs. Furthermore, our results depicted the smoother background which verifies that this filter is a high-smoothing filter, hence the loss in image detail and the degradation of contrast [4,26].…”
Section: International Journal Of Biomedical Imagingsupporting
confidence: 70%
See 1 more Smart Citation
“…However, with higher cutoff frequency, the image revealed two more pairs. Furthermore, our results depicted the smoother background which verifies that this filter is a high-smoothing filter, hence the loss in image detail and the degradation of contrast [4,26].…”
Section: International Journal Of Biomedical Imagingsupporting
confidence: 70%
“…Furthermore, it also indicated that the impact on image quality varies with respect to the size of hot regions as well as the count density in the region of interest which is the case in this study. Moreover, higher frequency corresponds to small regions and to abrupt changes in the count density of regions of interest [26][27][28][29].…”
Section: International Journal Of Biomedical Imagingmentioning
confidence: 99%
“…In this study, 120 projections were taken instead of 64 projections as recommended by IAEA. [11] Also stated by [12] that high number of projections could prevent formation of the star artefact and blurring of the image. For reconstruction of images, all acquired SPECT image data (with and without material filter) were processed by using filtered back projection technique.…”
Section: Methodsmentioning
confidence: 99%
“…However, the image quality is limited by a number of reasons; among them is noise [1]- [5]. Therefore, it is essential to carefully tackle this issue.…”
Section: Introductionmentioning
confidence: 99%
“…A higher order results in a sharper fall. However, both functions have a significant role to play in achieving a better quality image [5]- [7].…”
Section: Introductionmentioning
confidence: 99%